Alpers Syndrome with Hepatic Cirrhosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Four children, from two families, with fatal degeneration of the cerebral grey matter and terminal hepatic dysfunction are reported from the Royal Belfast Hospital for Sick Children, Northern Ireland.